Non-invasive imaging of fungal colonization and host response in the living sapwood of sycamore (Acer pseudoplatanus L.) using nuclear magnetic resonance - (:unkn) unknown (My University, 1994)
Non-invasive nuclear magnetic resonance (NMR) imaging techniques revealed anatomical features of healthy sycamore (Acer pseudoplatanus L.) stems, the pathological anatomy of sooty bark disease [Cryptoslroma corticale (Ell. and Everh.) Gregory & Waller] lesions, and the dynamics of fungal invasion and host response in excised lengths of living sycamore stems challenged with Ustulina deusta (Fr.) Petrak or Chondroslereum purpureum (Pers. ex Fr.) Pouz. Infected wood and reaction zones could be distinguished clearly from healthy tissue in these images. Lesion development, observed by the sequential imaging of individual stems, followed the course deduced from the destructive examination of a set of similar stem lengths. U. deusta was unable to penetrate far into the living stem lengths, and responses chemically and morphologically similar to the reaction zones formed at the margins of naturally occurring decay lesions were expressed at the interface between healthy and colonized xylem. In contrast C. purpureum rapidly invaded and killed excised stem lengths with little or no induction of characteristic reaction zone responses. Calculated proton density (Mo) images indicated that water levels in the reaction zones delimiting U. deusta lesions were elevated by a factor of approximately 2·5-3·0. No such accumulation of water occurred at the margin of C. purpureum lesions. The significance of this in relation to xylem defence against fungal attack is discussed. © 1994 Academic Press, Inc.